Influência do sexo sobre parâmetros hematológicos, bioquímicos e histopatológicos de ratos tratados com agomelatina associada a losartana, sinvastatina e metformina - Bachur, Tatiana Paschoalette Rodrigues (2020)
Knowledge about the potential of drugs to cause drug interactions is essential to patient safety and treatment efficacy. Losartan, simvastatin and metformin are among the most widely used drugs for the control of chronic degenerative diseases worldwide. At the same time, agomelatine appears as a recent therapeutic alternative for depression, with a relatively better safety profile than other antidepressants, although with a potential hepatotoxic effect. The objective of this study was to analyze the effect of the association of agomelatine (AGO) with losartan (LOS), simvastatin (SIN) and metformin (MET) on hematological, biochemical and histopathological parameters of Wistar rats, after subchronic treatment, and to evaluate the interference of associations in the antidepressant profile of agomelatine. Male (60) and female (60) Wistar rats were divided into 10 experimental groups (n = 6 / group) and treated per os, for 90 days, with saline (control), AGO (2.27mg / kg), LOS ( 4.61mg / kg), SIN (1.83mg / kg) and MET (78.66mg / kg) and their combinations (AGO + LOS, AGO + YES, AGO + MET, LOS + YES + MET and AGO + LOS + YES + MET). At the end of 90 days of treatment, the animals were subjected to the forced swim test. After euthanasia, hematological and biochemical parameters were evaluated and histopathological analyzes were performed on multiple organs. In hematological analyzes, the main changes were seen in the erythrogram. Females were more sensitive than males to the concomitant use of multiple drugs in relation to changes in hematological and biochemical parameters. Biochemical parameters related to liver and kidney function were the most affected. Agomelatine was related to an increased risk of histopathological changes in males and females when associated with other drugs, especially in the liver, kidneys and spleen. Females showed more intense and more severe liver histopathological changes when agomelatine was combined with simvastatin and metformin. Females were also more sensitive to renal histopathological changes and renal atrophy than males when using metformin as monotherapy or associated with agomelatine. The spleen was significantly affected, particularly in females, in line with the changes observed in the erythrogram. The antidepressant activity of agomelatine in males was significantly reduced with the concomitant use of metformin. The result of the forced swimming test signals the need to investigate potential interactions of agomelatine and other drugs that may lead to a decrease in its antidepressant activity.